Perkawinan Beda Agama dalam Undang-Undang Perkawinan dan Hukum Islam - Ermasyanti (Law Faculty of Universitas Bandar Lampung, 2011)
Cross religion marriage can be done according to article 66 of Marriage Law by applying Regeling op de gemengde Huwelijken (GHR) Staatsblad Â year - 1898 No. 153 which regulates cross religion marriage for Indonesian people which has different law. In Islamic compilation law, cross religion marriage is illegitimate and is not valid, the marriage between muslim men and non-muslim women is illegitimate and is not valid (qaul-muâtamad). Majelis Ulama Indonesia Decision (Fatwa MUI) No. 4/ MUNASVII/MUI/8/2005, Islamic law forbid cross religion marriage because its disadvantages are more than its advantages